ANALISIS FAKTOR PENDORONG PERILAKU PEMBELI YANG MEMPENGARUHI KONSUMEN DALAM KEPUTUAN PEMBELIAN (Studi pada Swalayan di Kota Blitar) - Denok Wahyudi Setyo Rahayu (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2018)
The purpose of this research is to examine factor that influence purchasing behavior of customer in purchasing decision at Blitar city. the indicators is product, price, place, and promotion. Marketing mix with partial and simultaneous can be result different it. By using regression with F-test, hypothesis are proved significant. Research study at department store in Blitar city to show if purchasing decision will be because mix from product, price, place, and promotion. With combination all can be selling good. So, owner must do it if will many much profit. Keywords: purchasing decision, product, price, place, promotion